Investigation into trapping modes and threshold instabilities of state-of-art commercial GaN HEMTs. (September 2019) - Mukherjee, K.; De Santi, C.; Rzin, M.; Gao, Z.; Meneghesso, G.; Meneghini, M.; Zanoni, E.
Abstract: This work is aimed at investigating the performance and reliability limits of a commercially available state-of-the-art RF GaN HEMT technology. Measurement strategies to recognize and assess trap-induced degradations, prevalent in mature technologies, are discussed. Double pulsed measurements are used to capture and quantify threshold instabilities, and their evolution with temperature, for short quiescent near-threshold and off-state stress conditions. A versatile transient measurement technique evaluates threshold voltage fluctuations in the 10 μs–100 s temporal range, during stress or recovery phases, for different trap-filling configurations. Corresponding recovery transients between 27 °C to 130 °C are analysed to extract a trap activation energy of 0.53–0.56 eV for this technology. Finally, drain and gate step-stress tests are performed, providing an overview into the robustness of the gate contact under high electric fields. Highlights: Pulsed and step stress analyses study trapping modes of commercial state-of-the-art RF GaN HEMTs. Transient measurement technique evaluates Vth fluctuations in the 10 µs-100 s temporal range. Negative and positive Vth drifts discussed. Deep levels with de-trapping constants > 100 µs identified. Recovery transients for 27- 130°C: trap EA = 0.53-0.56 eV. Gate and drain step-stress tests review robustness of gate contact: good tolerances to high fields observed.